PENILAIAN KINERJA PT. BANK JATIM CABANG PAMEKASAN DENGAN PENERAPAN METODE BALANCED SCORECARD - Wahyu Maulana; Citra Larashati Surya (J-MACC, 2019)
Balanced scorecard (BSC) is an alternative performance of measurement that aims at combining financial and non-financial performance measures. This measurement is the result of the process based on the mission and strategy of the company. There are 4 aspects measured including financial perspective, consumer perspective, internal business process perspective, then, growth and learning perspective. The data collection used secondary data obtained from the company's annual report from 2015 to 2017. This study aimed to determine how the performance of PT. Bank Jatim of Pamekasan Branch Office used BSC. By using the performance appraisal, it can be seen that the causal relationship between performance supporting factors and the results are achieved. It is expected that PT. Bank Jatim of Pamekasan Branch Office is able to become a trusted bank, have a good commitment, and be able to earn optimal profit. The results of this study indicate that the financial perspective shows a good performance. By the result obtained in the customers' perspective, it means that the performance is good enough. By the value generated in the perspective of this internal business process, the performance is good. Growth and learning perspectives show a good performance. Based on the overall results related to the percentage acquisition in each perspective of BSC assessed, thus, the performance of PT. Bank Jatim of Pamekasan Branch Office is rated well.